2018
DOI: 10.1155/2018/9257874
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin-Induced Insulin Resistance May Be Linked to Decreased Lipid Uptake and Lipid Synthesis in Human Skeletal Muscle: the LIFESTAT Study

Abstract: Background A prevalent side-effect of simvastatin is attenuated glucose homeostasis. The underlying mechanism is unknown, but impaired lipid metabolism may provide the link. The aim of this study was to investigate whether simvastatin-treated patients had a lower capacity to oxidize lipids and reduced expression of the major proteins regulating lipid uptake, synthesis, lipolysis, and storage in skeletal muscle than matched controls. Materials and Methods Ten men were treated with simvastatin (HbA1c: 5.7 ± 0.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Simvastatin-induced insulin resistance has been proposed to result from decreased lipid synthetic capacity in skeletal muscle. This may lead to intracellular accumulation of toxic fatty acid metabolites, which impairs insulin sensitivity ( 13 ). This observation is supported by the finding of larger lipid droplets in muscle cells of patients treated with statins ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simvastatin-induced insulin resistance has been proposed to result from decreased lipid synthetic capacity in skeletal muscle. This may lead to intracellular accumulation of toxic fatty acid metabolites, which impairs insulin sensitivity ( 13 ). This observation is supported by the finding of larger lipid droplets in muscle cells of patients treated with statins ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Statin use may restrain the improvements in mitochondrial oxidative capacity with exercise training . Although this could potentially reduce the capacity to oxidize fat, that effect has not been reported . To our knowledge, there are no studies addressing the acute effect of a bout of exercise on PPTG in individuals chronically treated with statins.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, statin use reduces skeletal muscle coenzyme Q10 content which could reduce mitochondrial oxidative capacity and potentially fat oxidation. The literature is unclear on the effects of prolonged statin use on fat oxidation during exercise with reports of depressed or unchanged fat oxidation …”
Section: Introductionmentioning
confidence: 99%
“…Muscle symptoms, such as fatigue, pain or weakness, are the most common statin side effects: these symptoms occur in up to 7% of statin users and up to 25% of statin users who participate in vigorous physical exercise [19]. Previous studies have shown that statin-induced muscle dysfunction is related to impaired mitochondrial function [2022], protein breakdown [23], reduced protein synthesis [24], decreased lipid uptake and synthesis [25] and increased ectopic lipid deposition [26]. Skeletal muscle accounts for the major glucose disposal site in the body, and impaired muscle viability or glucose uptake may result in a risk of diabetes.…”
Section: Introductionmentioning
confidence: 99%